Serviço Social e questão ambiental : desafio para a formação profissional na contemporaneidade - Oliveira, Tatiane Ropck Félix Mendes de (2013)
The thesis herein presented was made as a requirement titration MA in Social Policy at the Federal University of Mato Grosso, linked to the Department of Social and results of a research project addressing the issue of environmental issues relating to the new demands made to the work of social workers, requiring therefore their inclusion in the project of vocational training. The interest in studying environmental issues came from the understanding that environmental problems have been intensifying and affecting unequally the different sectors of society, being felt most strongly by the poorest segments and therefore become more vulnerable to speculation performed by capital, but also the consequences of environmental degradation, which often leads to loss of the means by which they carry out their social reproduction. This pro se already justifies the importance that should be given to this issue by the Social Service in view of the centrality of social issues in the design of existing training and professional intervention as part of the specialized work that through their professional practice, establishing relationship with the most varied forms of expressions of social issues, associated with how users experience them in their work, family, community, housing, health, public welfare. The study was based on a qualitative methodology informed by critical dialectical perspective through literature review and desk research. The result showed a rich debate in the literature on the subject of Social Sciences. In Social Services identified himself, from a historical retelling of training projects in the literature of the profession, that only the ABEPSS curriculum guidelines (1996) gave the opening theme of environmental issues was inserted in the curriculum of the courses of Service Social. The importance attached to environmental issues by Social Services has produced the first research which indicates its content still recent and incipient in the profession.